PENGEMBANGAN MEDIA INTERAKTIF BERBASIS GAME EDUKATIF PADA MATERI NILAI – NILAI PANCASILA KELAS V SDN SAMBIREJO 1 - Aurora Alfitri Damayanti Siswanto; Frans Aditia Wiguna; Kukuh Andri Aka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop an product Interactive learning Media Based on Educational Games on Pancasila Values ​​Material . This research uses the Research and Development research method. The ADDIE development model consists of five stages, namely 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Based on the results of this research, it can be seen that the Interactive Media Based on Educational Games has an average validity value from material experts and media experts of 90% which can be said to be very valid, the practicality value from the average practicality value for teachers and students is 97,1% which can be said to be very practical, the effectiveness value from the results of limited trials and extensive trials through post-test questions received a value of 91,25% which means it is very effective. Interactive Media Products Based on Educational Games on Pancasila Values obtained very valid, very practical and very effective results to use.